Study of heat transfer coefficient for multi-jet air impinging cooling - Mohammad Khyru, Aris (2009)
This thesis deals with a study of heat transfer coefficient for multi – jet air impinging cooling. Research and development for enhancement heat transfer using multi – jet air impinging cooling system shows variety possibilities. The required performance must be achieved in other to boost user satisfaction. The main objectives of this thesis are to study the effect of heat transfer coefficient by multi – jet impinging cooling system, and define the relationship between the heat transfer coefficient with the jet flow and the distance from exit nozzle to the heat source. The thesis described the methodology utilize and the result comparison among the jet used. Single, 4, and 9 jet nozzles with constant nozzle diameter, 4 mm were studied in this thesis with different jet flow and also various exit nozzle to heat source spacing. The heat source plate is constant at 100℃. Compressed Air as the coolant medium at room temperature with laminar flow at nozzle exit was studied along with 500, 950, 1960 and 2300 Reynolds numbers. From the results, it is observed that the experiment data using 9 jet array nozzle produced the highest Nusselt number in the range of 95 ℃ to 105 ℃ correspond to low temperature distribution due to many stagnation point formed. This shows the most efficient cooling system. The graph pattern shows the maximum and minimum point in view of the fact that there are many stagnation points. However, the single jet and 4 jet nozzle produced low Nusselt number. The Nusselt number graph trend is linearly decreased for single jet and linearly increased for 4 jet nozzle. The results concluded that the additional number of nozzle with higher Reynolds number and narrow spacing of exit nozzle to heat source plate being used, the more efficient performance produced. More stagnation point created during the impingement on the heat source will produced more effective cooling system. The experiment results are significant to improve the overheat component problem nowadays. The results can also significantly increase the performance of the needed component in order to improve product reliability and customer confidence.